Lean and CSR, contradictions and complementarities: Toward an effective managerial solution. Issue 4 (2nd October 2021) - Ivanaj, Silverster; Collet, Mélanie; Gendron, Corinne; Friser, Alice
Abstract: Lean management is a way for companies to improve their productivity and bring down their costs. Corporate Social Responsibility (CSR) aims to meet the expectations of stakeholders concerning a company's impact on the environment and society. Despite their importance, and sometimes their coexistence, companies tend to tackle these two approaches separately. In this study, which employs a qualitative survey of seven companies, we attempt to understand the synergies and possible contradictions between Lean and CSR approaches. Firstly, it is clear that Lean, like CSR, concerns the economy, the environment, and stakeholder relations. Secondly, when combined, these two approaches compensate for their respective shortfalls: Lean management makes it possible to justify CSR on economic and financial levels, and provides CSR with a rigorous methodology in terms of operational management. CSR brings Lean management a way to consolidate its social and environmental benefits, and brings meaning that fosters employee engagement and extends the intervention scope of Lean to external stakeholders. This study also highlights a common key success factor, i.e., a corporate culture aimed at excellence. On this basis, the study recommends the combined implementation of both approaches in order to maximize their respective benefits. Seen from this perspective, CSR could be considered as continuous improvement of the company's overall performance, the first step of which would be Lean.